Adopting European Union Legal Frameworks for Restructuring ASEAN: Pathways to Regional Stability - Isroni Muhammad Miraj Mirza; Oksha Dwi Anugrah Panjaitan; Andre Arya Pratama (Faculty of Law, Maranatha Christian University, 2024)
Eversince its establishment, ASEAN has adopted a strict approach in tackling regional issues known as the ASEAN WAY including its non-intervention principle. In that regard, it requires consensus from all ASEAN member states without exception, no matter how long it takes before such problems can be addressed through ASEAN as a regional organization. If consensus is unfeasible, the problems will remain unresolved. Issues inflicting Rohingya ethnic, South China Sea, etc., are prime examples on ASEAN’s weakness as an institution. Compared to the European Union as a Supranational Organization, it has a more systematic and flexible approach in solving regional issues. The purpose of this research is to analyze to what extent EU law is applicable within ASEAN’s organizational structure to ensure a robust ASEAN integration so that one day it can achieve the status of a supranational organization like the European Union. This research method uses a normative juridical approach by analyzing the principles and instruments of international law applicable within ASEAN organizational structure, one of which is the ASEAN CHARTER as a legal basis that applies for all ASEAN member states, and further to what extent EU Law (EU LAW) is applicable within ASEAN organizational structure. The conclusion in this study is enhancing ASEAN's effectiveness in tackling regional issues and quickly adapting to global challenges such as the European Union, ASEAN countries must ignore differences and concentrate on restructuring ASEAN by redefining ASEAN Way and the Non-Intervention Principle for stronger regional integration and stability.